Interactive technologies as a means of forming grammatical competence of future teachers of foreign languages - Ревенко, Вікторія Володимирівна (Pedagogy of Higher and Secondary Education, 2013)
Revenco V. V. Interactive technologies as a means of forming grammatical competence of future teachers of foreign languages. In the article the possibilities of interactive technologies as a means of developing future teachers’ grammar competence are analyzed. The author gives examples of using of interactive methods at the lessons of practical grammar of English.